Será que o patinho é feio? - Piacentini, Elisandra; Spolti, Silvani; Duarte, Cleonice; Basílio, Silvana; Bordinhão, Andréia Jonceline Chiozini; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf